City of light - Arthur, Keri (London : Piatkus, 2016)
When the bombs that stopped the species war tore holes in the veil between this world and the next, they allowed entry to the Others - demons, wraiths and death spirits who turned the shadows into their hunting grounds. Now, a hundred years later, humans and shifters alike live in artificially lit cities designed to keep the darkness at bay. As a dechet - a breed of humanoid super-soldiers almost eradicated by the war - Tiger has spent her life in hiding. But when she risks her life to save a little girl on the outskirts of Central City, she discovers that the child is one of many abducted in broad daylight by a wraith-like being - an impossibility with dangerous implications for everyone on Earth. Because if the light is no longer enough to protect them, nowhere is safe.
Keywords: Shapeshifting -- Fiction; Genetic engineering -- Fiction; Vampires -- Fiction; Australian